The deep-sea species of Triphoridae (Gastropoda, Triphoroidea) from Guadeloupe, sampled by the Karubenthos 2 expedition - Fernandes, Maurício Romulo (European Journal of Taxonomy, 2025)
This study aims to evaluate the taxonomic composition of the deep-sea triphorids from Guadeloupe obtained by the Karubenthos 2 expedition, which comprised 159 marine sampling events. The Karubenthos 2 sampled 14 deep-sea species of Triphoridae (i.e., species typically found below 200 m), which increases the number of deep-sea triphorids from Guadeloupe to 15. Three new species are described (Strobiligera pictasp. nov., S. variabilis sp. nov., S. cupella sp. nov.), six species were previously known only from the northern Caribbean or adjacent areas, one species (S. cf. delicata Fernandes & Pimenta, 2014) was previously known from SE Brazil, another species (S. dinea (Dall, 1927)) is widespread in the West Atlantic and only “Inella” longissima (Dall, 1881) was already recorded from Guadeloupe; two other morphs (Strobiligera sp. A, Strobiligera sp. B) remain without specific determination, requiring additional material. I formalize Norephora Gründel, 1975 syn. nov. as a junior synonym of Subulophora Laseron, 1958, which is probably related to Inella Bayle, 1879, but Strobiligera Dall, 1924 is regarded as a recent and derived group, restricted to deep waters of the Atlantic Ocean. Other taxonomic novelties in this study are: Costatophora numerosa(Jousseaume, 1898) comb. nov.; Euthymella sculpta (Hinds, 1843) comb. nov.; Strobiligera carioca sp. nov. (described from SE Brazil); Strobiligera colon (Dall, 1881) comb. nov.